Built environment and sustainability. Recycled materials and Design for Disassembly between research and good practices - Cesare Sposito; Francesca Scalisi (Agathón)
In the context of environmental emergency of which the construction sector is one of the main causes – since it consumes 40% of the (embodied and operational) energy and produces about a third of the total waste – and due to the ambitious objectives set by the international community and by many countries to reduce the environmental impact of buildings during their whole life cycle, this paper wants to make a contribution to the understanding of the state of the art on cycle-based research activities, sustainable experiments and good practices that the building industry and the academy have implemented in recent years.  In particular, it refers to cycle-based theoretical and experimental actions involving process and product innovations at different scales (‘macro’, ‘meso’ and ‘micro’) of the built environment. They are capable of overcoming the traditional linear approach to use an approach aiming, on the one hand, to extend the service life cycle, and on the other, to evaluate new bio-based materials, easily renewable and with a low embodied energy. In the end, the paper highlights the problems that currently hinder its dissemination and identifies possible research actions that can favour, with the contribution of Architectural Technology, the transition to this new paradigm.